Social Cognitive Theory as a Theoretical Framework to Predict Sexual Risk Behaviors among Older Adults. Issue 3 (27th May 2021) - Graf, Allyson S.; Cohn, Tracy J.; Syme, Maggie L.
ABSTRACT: Objectives: Older adults vary in their safe and unsafe sexual behaviors. While researchers are beginning to understand more about the sexual and intimate expression of older adults, only recently are they beginning to understand how older adults make decisions about sexual risk. Bandura's social cognitive theory offers a frame for understanding how self-efficacy, environmental factors, and goal motivation are related to sexual risk behaviors for older adults, including the interplay between these variables. Methods: Using a diverse sample of older adults ( n = 720) age 50+ years, social cognitive theory was modeled to determine the relationship between environment variables (age, gender, and sexual health conversations with practitioners), behavioral variables (self-efficacy), and cognitive variables (importance of sexual wellness goals) with the outcome variable of sexual risk behaviors. Results: Self-efficacy had an indirect effect on sexual risk via sexual wellness goal motivation. Healthcare provider conversations had both direct and indirect effects on older adults' sexual risk through sexual wellness goal motivation. Models were similarly predictive for older men and women. Conclusions: Sexual risk behaviors among older adults are more influenced by environmental factors in their healthcare settings and their perception and prioritization of sexual wellness goals. Clinical implications: Providers play a key role in initiating and maintaining sexual health discussions with older patients, potentially mitigating sexual risk and bolstering self-efficacy.